Particle-size controlled porous nano-flowers constructing 3D hierarchical mesoporous manganese dioxide: Template-free formation and capacitive performance. (January 2021) - Li, Shuang; Yu, Li-Li; Xu, Wei-ling; Li, Rong-bing; Zhu, Jun-Jie; Fan, Jun; Zhao, Jing-Tai
Highlight: Particle-size controlled porous nanoflowers forming hierarchical porous spongy-like MnO2 with high specific surface area of >300 m 2 g −1 are prepared in high yields at room temperature by a template-free way. The formation as well as particle size of porous nanoflowers are determined by the nucleation concentration in the initial reaction. The specific capacitance of mesoporous MnO2 with similar crystallizations and morphologies is proved to be determined by its specific surface area. Assembled MnO2 //AC capacitor delivers a high specific energy of 12.5 Wh kg −1 at 9 KW kg −1 with a cycling stability of 96% after 2000 cycles at 5 A g −1 . Abstract: Manganese dioxide porous nanoflowers are deemed as a potential supercapacitor electrode material due to its high surface-to-bulk ratio and abundant pore. In this paper, hierarchical porous manganese dioxide (MnO2 ) self-assembled by particle-size controlled porous nanoflowers with specific surface areas of > 300 m 2 g −1 are prepared at room temperature by a simple template-free approach. The formation of porous nanoflowers as well as their particle sizes are found to be determined by the nucleation concentration in initial reaction. And investigation on the electrochemical performance and microstructures demonstrates that the specific capacitance of mesoporous MnO2 with similar crystallizations and morphologies is mainly determined by their specific surface areas (SSAs). And sample with average particle size of 60 80 nm as well as SSA of 380 m 2 g −1 and a pore volume of 1.97cc g −1 exhibits the best electrochemical performance, a high specific capacitance of 245 F g −1 with excellent cycling stability of 99.1% after 5000 cycles at 5 A g −1 in 1 M aqueous Na2 SO4, due to its well-defined morphology with proper particle size, larger specific surface areas (SSA) and higher pore volume. Graphical abstract: Image, graphical abstract